Kinerja Bhabinkamtibmas dalam Mencegah Tindak Pidana Pencurian Kendaraan Bermotor di Wilayah Hukum Polsek Ciamis: Bhabinkamtibmas Performance in Preventing Crime of Motor Vehicle Theft in Ciamis Police Judirsdiction - Muhammad Farhan Arrafi (Police Studies Review, 2021)
The high number of curanmor crimes that occurred in the Ciamis Police Station was my background in carrying out this research. In this connection the community should receive education in the form of deterrence and deterrence power so that the crime does not occur. So this is related to the lack of or not yet implemented performance of Bhabinkamtibmas. This aims to describe and analyze the performance, the factors that influence it, and how to improve the ability of Bhabinkamtibmas in the Ciamis Police jurisdiction. The theory and concepts used in analyzing this research are role theory (Role Theory), motivation theory, competency theory, community policing concept, Bhabinkamtibmas concept, Bhabinkamtibmas skills concept, and promoter concept. This research method uses a qualitative approach with field research methods. This research is located in the jurisdiction of the Ciamis Police, with the focus of research on members of the Ciamis Police. This research uses data collection techniques, namely interviews, observation, and document review. The findings are (1) Bhabinkamtibmas performance is due to motivational factors such as performance allowances, Bhabinkamtibmas cannot have a more advanced career, and the level of security of Bhabinkamtibmas in touching community groups. (2) What affects the duties of Bhabinkamtibmas are internal factors and external factors. Apart from that, from the aspect of Bhabinkamtibmas skills regarding social communication, problem solving, leadership, negotiation and mediation, and early detection. (3) The ability of Bhabinkamtibmas in the fields of knowledge, skills, self-concept, self-characteristics, and motives requires improvement by involving the Ciamis Police, the West Java Regional Police and Higher Education in Ciamis. The performance of Bhabinkamtibmas is not optimal due to lack of motivation and in its implementation it seems that it is aborting duties, as well as factors that influence there are internal and external Bhabinkamtibmas. It is necessary to have more detailed control and supervision so that implementation is in accordance with the rules and can achieve security and order.